MACKINDER’S “HEARTLAND”: A HELP OR HINDRANCE IN UNDERSTANDING CENTRAL ASIA’S INTERNATIONAL RELATIONS? - MEGORAN, Nick; SHARAPOVA, Sevara (CENTRAL ASIA AND THE CAUCASUS, 2005)
In 1904 the British geographer Halford Mac-kinder (1861-1947) delivered a paper to London’s Royal Geographical Society entitled The Geographical Pivot of History. He argued that the “Pivot,” or “Heartland” of Eurasia—much of Russia and Central Asia (see Fig. 1)—was the key to the balance of power in the world, and the state that controlled it would be well-placed to dominate Eurasia and even the world. His ideas proved controversial but entered into the vocabulary of U.S. foreign policy during the Cold War. Some commentators predicted that the end of the U.S.-U.S.S.R. conflict would lay Mackinder’s thesis to rest. However, his ideas have experienced a renaissance in application to Central Asia. Numerous scholars and journalists have seen fit to revise his ideas, claiming that Central Asia, as the focus of a competition for influence from Russia, the U.S., China, Turkey, Iran and others, has taken its rightful place as the Pivot of Asia. Reducing the “Heartland” to Central Asia, Ehsan Ahrari contends that “the father of modern geopolitics, Sir Halford Mackinder, once said that whoever controlled Central Asia would wield enormous power in the world.”1 Basing their analysis on Mackinder’s theories, Sloan argues that “Central Asia is once more a key to the security of all Eurasia,”2 whilst O’Hara describes competition in Central Asia between external powers since 1991 as “the scramble for the ‘Heartland’,”3 and suggests that Mackinder’s “insightful observations may yet be proved correct.”4Others, however, have criticized this linkage. Edwards argues that it arbitrarily merges ideas about a “new great game” with geopolitics to make policy recommendations, without any attention to theoretical rigor or careful reading of the geopolitical tradition.5 Fettweis contends that the application of Mackinder’s ideas to contemporary Central Asia is profoundly misplaced, as they have been overtaken by the course of events, leading us to waste valuable foreign pol-icy opportunities.6